PENDEKATAN PEMROGRAMAN MULTIOBJEKTIF INTERAKTIF UNTUK MENYELESAIKAN MASALAH ALOKASI ASET OPTIMAL DAN STUDI KASUS PADA LIMA SEKURITAS DI INDONESIA - ., Sutrisno; Munawarroh, Dita Anies (MATEMATIKA, 2014)
. In this paper, we use an interactive multiobjective programming approach to solve an optimal asset allocation problem. This problem contains two objective functions which are function of expected return that will be maximized and function of risk that will be minimized. We gives a case study for this problem to find the optimal asset allocation for five securities in Indonesia. The approachmentthat was used in this paper gives the percentage of each of the given five securities that gives the optimalexpected return and the optimal risk